Harnessing Minor Millets (Paspalum scrobiculatum): Formulation and Nutritional Evaluation of Millet-Based Functional Foods - Prabhavati S. Erimani; Sharangouda J. Patil; Sadashiv S. O. (The Bioscan, 2026)
Millets are recognized as miracle cereals due to their vital role in human physiology, providing essential nutrients and supporting planetary health. The present study aimed to select minor millets, conduct physicochemical analysis, and develop a millet malt-based functional food. Considering availability, underutilization, local food security, and limited economic activity, Kodo millet (Strain No. RK 390-25, Paspalum scrobiculatum) was chosen. The grains were subjected to soaking, germination, and drying, followed by powder preparation. Physical evaluation included colour, thousand kernel weight, true density, bulk density, and porosity. Proximate analysis determined moisture, ash, crude fiber, protein, carbohydrate, calcium, and fat. Anti-nutritional factors (tannin, saponin, oxalate), hydrolytic enzymes (amylase, protease, L-asparaginase, L-glutaminase), and antioxidants (flavonoids, total phenols) were also assessed. For product formulation, Kodo millet malt was combined with wheat, Bengal gram, jaggery, cardamom, diamond sugar, dry ginger, and dry coconut. Seven trials were prepared with varying ratios of Kodo millet malt and wheat–Bengal gram mix, supplemented by minor ingredients. Sensory evaluation using the hedonic scale revealed that germinated sun-dried Kodo millet powder (RK 390-25) showed improved nutritional outcomes, including reduced carbohydrate, increased protein, and enhanced mineral bioavailability. Among the formulations, the 40:60 millet-to-mix ratio was found dry and bland, while four other trials demonstrated favorable sensory attributes. Physical characterization of millets is crucial for agricultural practices, food processing, storage, and product development, as parameters like seed size, density, and moisture influence machinery design and grain quality. The study highlights the nutritional potential of minor millets, their role in value-added food products, and their capacity to replace junk foods with nutrient-rich, economical alternatives. Promoting millet-based formulations can enhance consumer awareness, support local food security, and contribute to healthier lifestyles. Keywords Anti-nutritional factors, Hydrolytic enzymes, Junk foods, Millets, Nutri product, Physico-chemical, Sensory evaluation